There Is No Place Like Home: A Survey on Satisfaction and Reported Outcomes of a Home-Based Rehabilitation Program Among Orthopedic Surgery Patients. (December 2020) - Gagin, Roni; HaGani, Neta; Levy, Itay; Norman, Doron
Background: Home-based rehabilitation (HBR) was previously found to be associated with positive outcomes that are equal to inpatient rehabilitation. Few studies have examined the challenges patients are facing during rehabilitation and recovery and their satisfaction from HBR. Objective: The purpose of this study was to examine the overall satisfaction and reported outcomes of HBR. Methods: A telephone survey was conducted among 146 orthopedic surgery patients who participated in an HBR program, at the end of the HBR and 6 months after. The questionnaire included information about level of independence, satisfaction from HBR, and difficulties during HBR. Findings: The overall satisfaction was high (73.1%). Patients reported on improvements in level of independence between the time of hospital discharge, the end of the program ( P = .0001), and the 6 months follow-up ( P = .004). Long wait for beginning of HBR, being a widower, and residing in a facility or with a nonfamilial caregiver were associated significantly with less general well-being and independence. The repeated measures analysis showed age lower than 71 and private health insurance ownership were associated with a better recovery. The most common difficulties reported were physical difficulties, lack of function, and caregivers' burden. Conclusions: Patients and families need more emotional, social, and physical support during HBR. The increase in health services delivered in community settings requires a more clear-cut policy and supervision for HBR and the follow-up services.